2018
DOI: 10.1186/s12917-018-1398-z
|View full text |Cite
|
Sign up to set email alerts
|

Crossed beaks in a local Swiss chicken breed

Abstract: BackgroundCrossed beaks have been reported to occur in Appenzeller Barthuhn, a local Swiss chicken breed. The assumed causes for this beak deformity which are also seen in other bird species including domestic chickens, range from environmental influences to genetic factors. The aim of this project was to characterize the prevalence, the phenotype, and the underlying genetics of crossed beaks in Appenzeller Barthuhn chickens.ResultsThe estimated prevalence of 7% crossed beaks in Appenzeller Barthuhn was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
3
10
1
Order By: Relevance
“…The upper and lower jaw bones are part of the craniofacial bone tissue, and any changes to them may shape the development of a beak. In this study, we observed significant deflections of the maxilla and mandible, which were consistent with previous studies [3,5]. In Appenzeller Barthuhn chickens, cross-beaks were more likely to deflect to the right side [3].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The upper and lower jaw bones are part of the craniofacial bone tissue, and any changes to them may shape the development of a beak. In this study, we observed significant deflections of the maxilla and mandible, which were consistent with previous studies [3,5]. In Appenzeller Barthuhn chickens, cross-beaks were more likely to deflect to the right side [3].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed significant deflections of the maxilla and mandible, which were consistent with previous studies [3,5]. In Appenzeller Barthuhn chickens, cross-beaks were more likely to deflect to the right side [3]. Even though no different occurrence was observed between the left and right cross-beaks in this study, lower cross-beaks were found to be more likely to deflect to the right side.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations